INTELLECTUAL CAPITAL AND COMPANY VALUE IN MINING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Azimah Hanifah; Iskandar Zulkarnain; Riyanti; Dea Herliyana (PENANOMICS: International Journal of Economics, 2023)
This study is aimed at analyzing the influence of Intellectual Capital and Company Value on Mining Companies (Metal and Mineral Sub-Sector) listed on the Indonesia Stock Exchange (IDX) peride 2015-2020. The sample of this study used four companies obtained using the purposive sampling method, namely PT. Antam, PT Cita, PT. DKFT and PT Tins. The variables used, for the Dependent variable, namely Company Value (TobinsQ) and Independent variables (Intellectual Capital) which consist of Value Added Capital Employeed (VACA), Value Added Human Capital (VAHU), Stuctural Capital Value Added (SCVA) and Value Added Intelectual Coeficient (VAIC). The results of the VACA study have a positive and sig effect, VAHU has a negative and significant effect, STVA has a negative and significant effect and CVIA has a positive and significant effect. The value of R square of 0.384 means that 38.4 %. The value of the company is determined by the variable intellectual capitaland the remaining 61.6% is determined by other variables that did not participate in this study.